Puukuitususpension putkistovirtaus, viskositeetti ja häviökorrelaatiomalli - Korhola, Tapani (2010)
We measured pressure loss and velocity profile from pine and birch suspension flow in two straight PVC-tubes. The suspension consistencies were 0,5 %–4,0 % and tubes' radius were 105,2 mm and 191,6 mm. The velocity profiles were measured with pulsed ultrasonic Doppler velocimetry technique. Unusual laminar shaped profiles were discovered at low flow rates of birch suspension. With these profiles it was possible to calculate the actual viscosity for fiber suspension. In the analysis we discovered that the viscosity didn't depend on the flow velocity or geometry. It was possible to write a material law that describes the viscosity as a function of shear rate with two material related parameters: =eC n . We compared theoretical velocity profiles plotted with the described viscosity to actual measured velocity profiles. Good match between profiles supports the material law. In the measurements we weren't able to measure as high flow rates we wanted to be able study loss correlation model between flow rate and pressure loss in depth. Still it was possible to do a simple parametrization of the model and test how it scales between two pipes of different diameter. The model scaled well only for low fiber consistencies, for birch with consistencies 1,0 % and 1,5 % and for pine at the consistency of 0,5 %.